ALFF and ReHo Mapping Reveals Different Functional Patterns in Early- and Late-Onset Parkinson’s Disease - Yue, Yumei; Jiang, Yasi; Shen, Ting; Pu, Jiali; Lai, Hsin-Yi; Zhang, Baorong (Frontiers in Neuroscience, 2020)
Heterogeneity between late-onset Parkinson’s disease (LOPD) and early-onset Parkinson’s disease (EOPD) mainly reflected in the following aspects including genetics, disease progression, drug response, clinical manifestation and neuropathological change. Although many studies have investigated these differences related with clinical significance, the functional processing circuits and underlying neural mechanisms haven’t been entirely understood. In this study, regional homogeneity (ReHo) and amplitude of low-frequency fluctuation (ALFF) maps were used to explore different spontaneous brain activity patterns in the EOPD and LOPD patients. Abnormal synchronizations were found in the motor and emotional circuits of EOPD group, as well as in the motor, emotional and visual circuits of LOPD group. EOPD patients showed functional activity change in the visual, emotional and motor circuits, and LOPD patients only showed increased functional activity in the emotional circuits. In summary, desynchronization process in LOPD group was relatively strengthened, and the brain areas with changed functional activity in EOPD group was relatively widespread. The results might point out different impairs in the synchronization and functional activity for the EOPD and LOPD patients.